Efektivitas Penggunaan Antimicrobial Dressing Terhadap Lama Proses Penyembuhan Luka pada Pasien Ulkus Kaki Dabetik di Pelayanan Kesehatan Wilayah Kabupaten Bekasi - Arifah Rakhmawati; Dewi Purnamawati; Wati Jumaiyah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Diabetic foot ulcers with infection are a chronic complication that is often found in people with Diabetes Mellitus. One nursing intervention to overcome this is by treating wounds using antimicrobial dressings such as silver, PHMB, DACC, and honey. The purpose of this study was to determine the effectiveness of the use of antimicrobial dressings on the duration of the wound healing process in diabetic foot ulcer patients in Bekasi district health service. This research used a quasi experiment design. The sample size in this study was 84 respondents. The ANOVA test results showed that the average difference between the duration of the wound healing process for types of silver, PHMB, DACC and honey with a p-value of 0.0001